PENGARUH PROMOSI TERHADAP PENGAMBILAN KEPUTUSAN DALAM PEMBELIAN AIR MINUM KEMASAN PADA PENJUAL PRODUK AIR MINUM KEMASAN MEREK SEDUDO DI NGANJUK - Marjoto Marjoto (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2014)
In general, every company is required to always strive to create a sustainable competitive advantage lot emergence of new competitors, and the company should be more responsive to the opportunities that clicking profitable and also have to know and learn everything related to the market and consumers, especially to keep survive in a competitive competition. Thus, competition between brands of each product will be sharp in win consumers. Based on the research results of the analysis in this study several conclusions can be made as follows. Based on the results of the study found that the influence on purchase decisions bottled water brand products sedudo on bottled water sellers sedudo brand in Nganjuk. Based on the research results that the overall variable advertising, sales promotion and relationship the purchase of bottled water products on the seller sedudo brand bottled water sedudo brand in Nganjuk.